APLIKASI MANAJEMEN DINAS PARIWISATA, PEMUDA, DAN OLAHRAGA KABUPATEN PANGKAJENE KEPULAUAN - Nur Inda Sari; Raharjo, Muh. Fajri; Amhar Davi Dewantara (Politeknik Negeri Ujung Pandang, 2025)
The Pangkajene Kepulauan (Pangkep) Regency Tourism, Youth, and Sports Office Management Application is an information system that includes four main features, which are adjusted to the four fields under the auspices of the Pangkep Regency Tourism, Youth, and Sports Office, namely: Tourism, Creative Economy, Youth, and Sports. This application is designed as a form of e-government implementation, with the aim of realizing good governance through the use of technology. This information system plays an important role in increasing organizational efficiency, while facilitating the use and processing of data. The results of the implementation and testing of this application show that the application was successfully developed according to the initial planning and functions as it should. This application acts as a management system for the admin of the Pangkep Regency Tourism, Youth, and Sports Office, as well as being a source of information for the public regarding Tourism, Creative Economy, Youth, and Sports in Pangkep Regency. This is proven through testing using the black box testing method on the admin which produces positive results, as well as testing with the SUS (System Usability Scale) method which gives a grade A with an Excellent interpretation at the level of public satisfaction. In the future, it is hoped that this application will continue to be useful for the Tourism, Youth, and SportsOffice of Pangkep Regency as an initial step towards implementing egovernment, as well as becoming an information system that makes things easier for the public